2018
DOI: 10.12968/ajmw.2018.12.3.121
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the use of facility-based birthing services in rural northern Ghana: A qualitative study

Abstract: Background: Use of facility-based birthing can reduce maternal mortality rates; however, service uptake is still poor in rural Ghana. Aims: To analyse key stakeholders' views on barriers to facility-based birthing in the Bongo district of rural northern Ghana. Methods: The study used a qualitative design. A purposive sampling technique was used to recruit 45 women from three communities for the study, plus four health professionals and two policy-makers. Data were collected through in-depth interviews and focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…It also boosts the woman’s appetite since the fruits contain Vitamin C, which is good for immunity. A similar finding was reported in a recent research study conducted in Ghana to explore the reasons associated with home births, expressing the point that lack of culturally acceptable food during childbirth in health facilities was one of the main reasons that accounted for women decided to give birth at home 23. The findings of this study highlighted the need for skilled birth care providers in rural areas to encourage women to be given culturally accepted nutritious foods during labor and after delivery.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It also boosts the woman’s appetite since the fruits contain Vitamin C, which is good for immunity. A similar finding was reported in a recent research study conducted in Ghana to explore the reasons associated with home births, expressing the point that lack of culturally acceptable food during childbirth in health facilities was one of the main reasons that accounted for women decided to give birth at home 23. The findings of this study highlighted the need for skilled birth care providers in rural areas to encourage women to be given culturally accepted nutritious foods during labor and after delivery.…”
Section: Discussionsupporting
confidence: 87%
“…Our study reinforces the findings of a recent study carried out in the northern part of Ghana to explore the barriers to utilization of skilled birth care. It discovered in that study that safe disposal of the placenta at home according to the dictates of tradition after birth was one of the reasons that accounted for the choice of home births 23. Our study participants held the view that the way the placenta is disposed of greatly determines the destiny and prospects of the child in later life.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have consistently reported women perception of quality of care provided by TBAs as a major setback to achieving the goal of reducing maternal mortality in rural communities in developing countries such as Ghana [24][25][26][27][28]. For instance, a recent study conducted in Ghana reported that women continued to give birth at home because of the perception that TBAs give better care as compared to the poor quality of care at health facilities in the rural areas [29]. These findings highlight the importance of collaborative maternity care between skilled birth attendants and TBAs in order to meet the needs of labouring women and as well reduce maternal mortality in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have consistently reported women perception of quality of care provided by TBAs as a major setback to achieving the goal of reducing maternal mortality in rural communities in developing countries such as Ghana [24][25][26][27][28]. For instance, a recent study conducted in Ghana reported that women continued to give birth at home because of the perception that TBAs give better care as compared to the poor quality of care at health facilities in the rural areas [29]. These ndings highlight the importance of collaborative maternity care between skilled birth attendants and TBAs in order to meet the needs of labouring women and as well reduce maternal mortality in rural areas.…”
Section: Discussionmentioning
confidence: 99%